2021
DOI: 10.3390/toxics9020022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acid-Base Status on Mortality in Patients with Acute Pesticide Poisoning

Abstract: We investigated clinical impacts of various acid-base approaches (physiologic, base excess (BE)-based, and physicochemical) on mortality in patients with acute pesticide intoxication and mutual intercorrelated effects using principal component analysis (PCA). This retrospective study included patients admitted from January 2015 to December 2019 because of pesticide intoxication. We compared parameters assessing the acid-base status between two groups, survivors and non-survivors. Associations between parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In addition, in the present study, glufosinate ingestion was identified as an important risk factor for acute respiratory failure; the incidence rate of respiratory failure in glufosinate poisoning is the same as that of organophosphate and carbamate. Intriguingly, given the comparable incidence of respiratory failure, patients who were intoxicated with organophosphate and carbamate showed respiratory acidosis at emergency room, but this was not observed in glufosinate poisoning [4]. In this study, it was revealed that the development of respiratory failure in glufosinate poisoning was slightly delayed (6 h later) as compared to organophosphate and carbamate, therefore, respiratory failure was not captured at the emergency department in cases of glufosinate intoxication.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, in the present study, glufosinate ingestion was identified as an important risk factor for acute respiratory failure; the incidence rate of respiratory failure in glufosinate poisoning is the same as that of organophosphate and carbamate. Intriguingly, given the comparable incidence of respiratory failure, patients who were intoxicated with organophosphate and carbamate showed respiratory acidosis at emergency room, but this was not observed in glufosinate poisoning [4]. In this study, it was revealed that the development of respiratory failure in glufosinate poisoning was slightly delayed (6 h later) as compared to organophosphate and carbamate, therefore, respiratory failure was not captured at the emergency department in cases of glufosinate intoxication.…”
Section: Discussionmentioning
confidence: 63%
“…Pesticide poisoning is characterized by high mortality compared with other poisonings [23], but fatality of agricultural pesticides after self-poisoning pesticide poisoning depends on the class of pesticides [24]. There are some studies on mortality prediction in acute pesticide poisoning [3,4,25]. In common clinical situations, scoring systems for patients in intensive care unit have been developed and introduced during the last over 30 years [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, preoperative acidosis can be linked to coagulopathy [ 8 ]. It is depicted that acidosis is a potential cause of coagulopathy, and hemorrhage resulting from coagulopathy increases intraoperative mortality among patients with ruptured hip fractures [ 25 ]. Various levels of AG are substantially related to different incidence rates of coagulopathy, which could provide supportive evidence for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…A principal component analysis, one of the methods to reduce dimensionality, is performed to reduce and nd the principal components from many variables. We previously reported the principal components associated with death in patients using pesticide components [12]. Meanwhile, a factor analysis, which consists of exploratory factor analysis (EFA) and con rmatory factor analysis [13] is a well-known statistical method in the eld of psychology to extract latent variables, namely factors, from surveillance data [14].…”
Section: Discussionmentioning
confidence: 99%